Recovery lines in ancient Egyptian child mummies: Computed tomography investigations in European museums. (1st March 2022) - Panzer, Stephanie; Schneider, Karl O.; Zesch, Stephanie; Rosendahl, Wilfried; Helmbold‐Doyé, Jana; Thompson, Randall C.; Zink, Albert R.
Abstract: The aim of this study was to investigate the prevalence and anatomical distribution of recovery lines (growth arrest lines) in ancient Egyptian child mummies. Whole‐body computed tomography (CT) examinations of 21 ancient Egyptian child mummies from European museums were evaluated for estimation of age at death and sex of the children. CT examinations were systematically assessed for recovery lines by inspection for metaphyseal lines, diaphyseal transverse lines, and bone‐within‐bone appearance at several sites of the skeleton. The estimated age at death of the children ranged from about 1 year to the age of 12–14 years. Twelve children were assessed as male, seven as female, and in two, the sex was indeterminate. Recovery lines were found in 18 out of the 21 (86%) child mummies. Metaphyseal lines were present in 12 mummies (57%), diaphyseal transverse lines in 12 mummies (57%), and bone‐within‐bone appearance in 11 mummies (52%). One case showed particularly dense metaphaseal bands typical of lead lines in lead poisoning. In conclusion, systematic assessment of recovery lines on CT images of ancient Egyptian child mummies showed a high prevalence of these lines. Many children had a combination of different lines, indicating more than one episode of growth disturbance. The spectrum of recovery lines included the better known metaphyseal and diaphyseal transverse lines as well as the less known bone‐within‐bone appearance that share the same pathomechanism. The mummy with lead lines seems to be the first case of radiological evidence of lead poisoning from ancient Egypt.